Analysis of Orthopedic Case Distribution Based on Gender, Treatment Status, and Type of Musculoskeletal Problems at the Hospital of Indonesian Red Cross in Southeast Sulawesi - Rizkia Milida; Rizkita Nur Ainun; Wa Ode Syamsara Sariwaty (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The hospital of the Indonesian Red Cross in Southeast Sulawesi (H-ICR-SES) is a private hospital serving as the center of orthopedic services in Southeast Sulawesi. The orthopedic clinic was one of the units with the highest number of visits at the hospital in 2025. The implementation of Electronic Medical Records (EMRs) in the orthopedic clinic has improved the effectiveness, accuracy, and efficiency of services, providing easier access to patient data and clinical decision-making. This situation highlights the importance of analyzing the distribution of orthopedic cases by gender, treatment status, and type of musculoskeletal problem. Objective: To analyze the distribution of musculoskeletal problem cases according to treatment status, gender, and type of musculoskeletal problem to support more effective and efficient service planning in H-ICR-SES. Methods: This analysis uses a descriptive design presented through the frequency distribution of orthopedic cases at the H-ICR-SES during the period January-September 2025. Data were obtained secondarily using a non-probability sampling technique. Results: The study indicated that the majority of orthopedic cases occurred in outpatient settings (75.8%), with the highest proportion being fractures, both in outpatient settings (39.2%) and inpatient settings (29%). Orthopedic cases were more common in men (63.3%). Conclusion: This study indicates that orthopedic cases at the H-ICR-SES are predominantly outpatients, with fractures being the most common type of case. The distribution of cases was greater in men, which is thought to be related to their greater physical activity and risk of trauma compared to women. Keywords: private, electronic health records, clinical decision, fractures, bone